Neuralgic amyotrophy: An update on diagnosis, pathophysiology, and treatment. Issue 3 (20th January 2016) - Van Eijk, Jeroen J.J.; Groothuis, Jan T.; Van Alfen, Nens
ABSTRACT: In this review we provide a current overview of the clinical features, pathophysiology, epidemiology, and diagnostic and therapeutic strategies in neuralgic amyotrophy (NA). The disorder has several phenotypic variations, with a classic form in 70% of the patients. It is not rare, with an incidence of 1 per 1, 000 individuals, but it is still often missed. Recurrences are common, yet the proposed multifactorial etiology, which includes genetic, biomechanical, and immunologic factors, limits our capacity to predict or prevent them. NA is a clinical diagnosis, and ancillary studies serve to exclude infectious or malignant causes or to assess a differential diagnosis. If patients are seen early and are still in pain, a short trial of high‐dose oral corticosteroids is advised, and adequate analgesia may require opioids and non‐steroidal anti‐inflammatory drugs. Persistent complaints are common, and a multidisciplinary rehabilitation approach focusing on scapular coordination, energy distribution strategies, and self‐management is indicated. Muscle Nerve 53: 337–350, 2016